Research on Energy Management Strategy of Pure Electric Vacuum Vehicle Based on Fuzzy Control - Wang, Yujie; Lei, Yu; Zhang, Licheng; Zhong, Shengshi (Frontiers in Energy Research, 2022)
The pure electric vacuum vehicle is equipped with main and auxiliary motors, and the two motors work independently without affecting each other. The traditional auxiliary motor usually operates with constant power, and the energy loss is large, while the main motor does not consider the bodywork system, and the matching degree of working conditions is low. Therefore, formulating a reasonable strategy for the two motors has a significant effect on the performance of the vacuum vehicle. This paper takes a pure electric vacuum vehicle as the research object and proposes an energy management strategy based on fuzzy control. First, for the work motor, a fuzzy controller with vehicle speed and acceleration as input and motor speed and torque as output is established, so that the vacuum vehicle can automatically adjust the operating power of the bodywork system according to the real-time road conditions; the drive motor control strategy adopts a closed-loop control strategy that combines driver input and vehicle state parameter feedback based on considering the operating motor. Finally, the effectiveness of the strategy is verified by simulation. The results show that the energy-saving control strategy effectively reduces the power consumption per 100 kilometers and increases the driving range, which is of great significance to the development and design of the vacuum vehicle.